Post-melting oxidation of highly primitive basalts from the southern Andes. (15th March 2020) - Tassara, S.; Reich, M.; Cannatelli, C.; Konecke, B.A.; Kausel, D.; Morata, D.; Barra, F.; Simon, A.C.; Fiege, A.; Morgado, E.; Leisen, M.
Abstract: The oxygen fugacity ( f O2 ) of the Earth's upper mantle and its melting products is an important parameter in the geochemical evolution of arc magmas and their connection with the continental crustal construction and growth. Several works have focused on the f O2 of peridotite xenoliths, primitive melts in relatively young arc settings, and mid-ocean ridge basalts (MORB) but few studies have attempted to examine the early redox history of primitive magmas in mature arcs. Hence, our understanding of the nature and evolution of f O2 during the subduction cycle remains limited. Here, we investigate the basaltic tephra from the Los Hornitos monogenetic cones in central-southern Chile, which are among the most primitive materials reported in the Southern Andes (olivine Mg# ≤ 92.5, and Ni ≤ 5000 µg·g −1 ). These features offer a unique opportunity to explore the f O2 conditions below the Andean arc by studying olivine phenocrysts and their contained crystal and melt inclusions. We integrated EPMA, LA-ICP-MS, and µ-XANES analyses to constrain the redox conditions recorded in the basaltic tephra by three different and self-reliant methods. First, we determined the f O2 based on the olivine-spinel equilibrium, yielding average values ΔFMQ + 1.3 ± 0.4 (1σ). Second, we constrained the f O2 conditions of melt inclusions using Fe µ-XANES data and the redox dependent olivine-melt vanadium partitioning. After correcting for post-entrapment crystallization and diffusive iron loss, the Fe µ-XANES data indicate that the melt inclusions were trapped in average at ΔFMQ +2.5 ± 0.5 (1σ). Results using the olivine-melt vanadium partitioning oxybarometer in melt inclusions are in agreement with Fe µ-XANES data, yielding average ΔFMQ values of +2.6 ± 0.3 (1σ). In order to test the potential effects of other post-entrapment modifications of the melt inclusions that could have affected the f O2 prior to eruption, we assessed the residence time of these magmas using Mg-Fe interdiffusion modelling in olivine. The short residence times (<200 days) compared to vanadium re-equilibration models strongly suggest that the melt inclusions preserve the prevailing f O2 conditions during their entrapment. Correlations between melt inclusions major element composition and their f O2 determined by Fe µ-XANES, as well as V/Sc modelling reveal a case of post-melting oxidation of the LHC magmas. We argue that primitive arc magmas behave as an open system with respect to f O2 during their early geochemical evolution. Our data indicate a complex f O2 early history of primitive melts in the southern Andes and provide a cautionary note on the direct extrapolation of primitive melts f O2 values to that of their mantle source.